O papel dos processos de rearranjo de drenagem na morfogênese neógena da alta/média bacia hidrográfica do rio Branco - Franzmiller Almeida Nascimento (2020)
The Amazon region, located in its own geographical context, stands out for its splendid mosaic of landscapes. However, the northern portion of this region, especially the State of Roraima, presents a wealth of unique landscapes even more diversified with emphasis on the region of the Gran Savanna. In this context, the state of Roraima is marked by a diversification of landscapes, differentiating itself from other regions of the Brazilian Amazon. Within this scenario, the hydrographic basin of the Branco River stands out, which representes the regional base level and drains a large part of the State of Roraima and the area bordering the Amazon River, Orinoco (Venezuela) and Essequibo (Guyana) basins. However, despite its high environmental importance, the basin presents few geomorphological studies that sought to understand its morphogenesis, including with regard to the importance of fluvial processes for regional evolution. In this context, the main objective of this study is to identify the processes that influenced the neogeneous geomorphological evolution of the upper/middle course of the Rio Branco basin through morphotectonic analyses and fluvial captures in the drainage network, based on remote sensing images, morphometric and field data. The methodological procedures used in the research were: a) pratical field work to verify morphological feactures, drainage rearrangements and relief characterization; b) bibliographical and cartographic survey, interpretation of remotely sensed images from satélites LANDSAT-8, 30x30 meters, sensor OLI and SENTINEL-2, 10x10 meters, sensor MSI, together with morphometic data obtained from MDE’s ALOS/PALSAR, 12.5x12.5 meters and SRTM, 30x30 meters and c) maping of geomorphological compartments and geomorphic surfaces, characterizing them and identifying the associated processes. The results obtained, indicates two large drainage anomalies (elbows) that practically prove a fluvial piracy that caused the Amazon basin to incorporate the entire northern portion of the Rio Branco basin, which was previously directed to the Caribbean Sea. This reorganisation of the local drainage network favored the formation of scaled Geomorphic Superficies, resulting from the processo of erosive carving of the Rio Branco. The interpreted data indicate that the fluvial system of the middle/lower course of the Uraricoera and Tacutu rivers presented endorheism, proven in the Maú, where the formation of a network of distributary palaeochannels stands out, constituting features of aluvial fans, these channels being tributaries of the Rupununi River (Essequibo basin). Subsequently, as a result of an apparent change in the regional base level of the Branco River, it favored the reorganization of the local drainage systems and consequently, promoting landscape changes.